Features of the Clinic and Treatment of Heroin Addiction in Patients with Psychopathic Personality Traits (Eurasian Research Bulletin, 2023)
In the last decade, it has been widely believed that drug addiction is more often formed in people with character abnormalities and mental illnesses. It is noted that drug addiction can be formed in different ways in people with various pathological manifestations of personality. There are also observations that some pathoharacterological types, regardless of the presence of decompensation, may occur more often with one or another type of dependence on psychoactive substances.